Enhancing the Inference Skills of Selected AP (Araling Panlipunan)-Grade 7 Students at OCABIS (Old Cabalan Integrated School): A Study Utilizing the Snake and Ladder Board Game - Maricel P. Gregorio; Dante P. Sardina; Allen Dale V. Olonan (Journal of Elementary and Secondary School, 2024)
The integration of game-based learning has gained popularity for enhancing cognitive skills such as critical thinking and inference. Interactive tools such as board games nurture engagement and assist in comprehending complex concepts. The Araling Panlipunan curriculum in the Philippines emphasizes critical thinking, making innovative teaching methods essential. This study aimed to determine the effectiveness of using the snake and ladder board game in enhancing the inference skills of Grade 7 Emerald students from the Old Cabalan Integrated School (OCABIS) in Araling Panlipunan (Social Studies) during the 2023-2024 academic year. The study employed a convergent parallel approach that included pre-tests, post-tests, and focus group interviews to collect data. Statistical analyses were used to examine the results, including frequency distribution, percentage, mean, Shapiro-Wilk test, Mann–Whitney U test, Wilcoxon signed-rank test, and thematic analysis. The results revealed that integrating the snake and ladder board game positively impacted students' critical thinking and inference skills, with post-test scores showing significant improvement as it revealed a notable enhancement in scores, showing a median pre-test score of 8 and a post-test score of 12 (W = 630.000, z = -5.184, p = .000), resulting in a moderate effect size (d = .62). The study also found that the board game strategy was equally effective for male and female students, providing a more engaging learning environment and reducing boredom. Based on these findings, the researchers proposed guidelines for further improving the snake and ladder board game strategy to enhance students’ inference skills.